Between the sound and sea : [large type] a novel - Cox, Amanda, 1984- (Thorndike Press large print Christian fiction series., 2025)
"Josephina "Joey" Harris wouldn't mind if her family still had a few secrets of their own after a lawsuit tarnishes their name. When an opportunity opens to become a temporary keeper of a decommissioned lighthouse on a North Carolina island, she takes the opportunity to escape the scrutiny of her small town to oversee its restoration. When things start to go amiss on the island, locals are convinced that it is the ghost of the lighthouse keeper and his daughter who were lost at sea during World War II. As Joey sifts through decades of rumors and legends and puts together the pieces of the past, a love story emerges, one that's clearly not over yet."--Back cover.